Coordinated regulation of myeloid cells by tumours - Gabrilovich, Dmitry I. (2012)
Myeloid cells are the most abundant nucleated hematopoietic cells in the human body and are a collection of distinct cell populations with many diverse functions. The three groups of terminally differentiated myeloid cells — macrophages, dendritic cells and granulocytes — are essential for the normal function of both the innate and adaptive immune systems. Mounting evidence indicates that the tumour microenvironment alters myeloid cells and can convert them into potent immune suppressive cells. Here, we consider myeloid cells as an intricately connected, complex, single system and we focus on how tumours manipulate the myeloid system to evade the host immune response.